KINERJA RANTAI PASOK SAYURAN DAN PENERAPAN CONTRACT FARMING MODELS - I. Rani Mellya Sari; Ratna Winandi; Netti Tinaprilla (MIX: JURNAL ILMIAH MANAJEMEN, 2017)
Abstract. A good supply chain requires strong collaboration, coordination, andintegration within each components of the chain involved. Such role is held by PTBimandiri Agro Sedaya as a driven between farmers and modern market. However, inthe marketing process, PT Bimandiri has a problem in the lack of supply of vegetablesallegedly due to lack of vegetables produced by partner farmers. This study aimed toanalyze performance of vegetable supply chains and contract farming partnerships inPT Bimandiri Agro Sedaya. Data processing method are Supply Chain OperationReference (SCOR) analysis, and Contract Farming Models analysis with respondents20 partner farmers and staff of PT Bimandiri. The results of chain performancemeasurements showed attribute of reliabilities in the advantage position so that theperformance of the supply chain of vegetables should be improved. Attributes ofresponsiveness and flexibility of the firm in a superior position. The result of a suitableagricultural partnership contract analysis to support supply chain performance is theCentralized Model. The company buys vegetables from farmers and then packs thevegetables to distribute to the modern retail. Strategic efforts that done to improvesupply chain performance by building cooperation with suppliers.Keywords: contract farming, SCOR, supply chain, vegetable